2019
DOI: 10.3390/en12030526
|View full text |Cite
|
Sign up to set email alerts
|

Application of Hydrodynamic Cavitation for Improving Methane Fermentation of Sida hermaphrodita Silage

Abstract: Hydrodynamic cavitation was recently applied as a biomass pretreatment method. Most of the studies which used hydrodynamic cavitation were applied to pretreated sugarcane bagasse or reed. High biomass yield of Sida hermaphrodita points out the necessity of studies on its effective pretreatment before methane fermentation, especially because its “wood-like” characteristics could present different disintegration properties than other lignocellulose biomass. Thus, the aim of the study was to investigate the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…More recently, some authors have recommend harvesting S. perfoliatum to maximise biogas production when the dry matter content is specifically 26-28% [81] or 30% [88]. A variety of pre-treatments to increase biogas production have been applied prior to the anaerobic digestion of S. hermaphrodita: chemical hydrolysis [137], chemical and enzymatic hydrolysis [139][140][141], mechanical, chemical plus enzymatic hydrolysis [142], as well as various mechanical [138,143,144], thermal [32,[145][146][147], and thermochemical treatments [148]. Ensiling of S. hermaphrodita is common practice prior to anaerobic digestion [42,67].…”
Section: Growing Sida Hermaphrodita and Silphium Perfoliatum As Solidmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, some authors have recommend harvesting S. perfoliatum to maximise biogas production when the dry matter content is specifically 26-28% [81] or 30% [88]. A variety of pre-treatments to increase biogas production have been applied prior to the anaerobic digestion of S. hermaphrodita: chemical hydrolysis [137], chemical and enzymatic hydrolysis [139][140][141], mechanical, chemical plus enzymatic hydrolysis [142], as well as various mechanical [138,143,144], thermal [32,[145][146][147], and thermochemical treatments [148]. Ensiling of S. hermaphrodita is common practice prior to anaerobic digestion [42,67].…”
Section: Growing Sida Hermaphrodita and Silphium Perfoliatum As Solidmentioning
confidence: 99%
“…Kisielewska et al [149] also demonstrated the effectiveness of ultrasound in increasing solubilisation and biogas production from a mix of S. hermaphrodita and cattle manure, obtaining methane yields of up to 337.9 dm 3 kg −1 oDM. After applying hydrodynamic cavitation to a mix of S. hermaphrodita and cattle manure for 20 min, Zieliński et al [144] produced a maximum methane yield of 439.1 dm 3 kg −1 DM. They recorded the highest process efficiency for the 5 min treatment, which increased biogas production by 30%.…”
Section: Growing Sida Hermaphrodita and Silphium Perfoliatum As Solidmentioning
confidence: 99%
“…Hydrodynamic disintegration has previously been successfully used for disintegration of sewage sludge [8,10,11]. This has led to attempts to use HD in the pre-treatment of feedstock in agricultural biogas plants, although reports regarding this are still scarce [9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The cited authors used pig slurry and energy crops (maize silage and triticale silage) as feedstock, and agricultural by-products (beet molasses, and corn meal) as supplementary biomasses. Hydrodynamic disintegration was also used to pre-treat Sida hermaphrodita silage mixed with cattle manure [13]. An increase in methane production by 14.7% and 29.4% was obtained with an energy profit of 0.14 Wh/g TS and 0.17 Wh/g TS for HD conducted in 2.5 min and 5 min, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation